Regulation of Sox9 by Sonic Hedgehog (Shh) is essential for patterning and formation of tracheal cartilage. - Wegner, Michael; et al. (Developmental Dynamics, 2010)
We report that Sonic Hedgehog (Shh) regulates both formation and patterning of tracheal cartilage by controlling the expression pattern and level of the chondrogenic gene, Sox9. In Shh-/- tracheo-esophageal tubes, Sox9 expression is transient and not restricted ventrally to the site of chondrogenesis, and is absent at the time of chondrogenesis, resulting in the failure of tracheal cartilage formation. Inhibition of Hedgehog signalling with cyclopamine in tracheal cultures prevents tracheal cartilage formation, while treatment of Shh-/- tracheal explant with exogenous Shh peptide rescues cartilage formation. Both exogenous Bmp4 and Noggin rescue cartilage phenotype in Shh-/- tracheal culture, while promoting excessive cartilage development in wild-type trachea through induction of Sox9 expression. The ventral and segmented expression of Sox9 in tracheal primordia under Shh modulated by Bmp4 and Noggin thus determine where and when tracheal cartilage develops. These results indicate that Shh signalling is a critical determinant in tracheal cartilage development. © 2009 Wiley-Liss, Inc.
UnivIS-Import:2015-03-09:Pub.2010.med.IB.LPCIPDBI.regula
Keywords: Mouse; Shh; Sox9; Tracheal cartilage